The Morality of Risk Modeling - Scordis, Nicos A. (2011)
This article applies the concept of prudence to develop the characteristics of responsible risk-modeling practices in the insurance industry. A critical evaluation of the risk-modeling process suggests that ethical judgments are emergent rather than static, vague rather than clear, particular rather than universal, and still defensible according to the discipline’s established theory, which will support a range of judgments. Thus, positive moral guides for responsible behavior are of limited practical value. Instead, by being prudent, modelers can improve their ability to deal with the ethical and technical complexity of the risk-modeling process. While the application of prudence to resolve ethical challenges in risk modeling, an issue of practical importance to managers, is a first in the literature, the practice of applying an ethical lens to issues of pragmatic importance for managers is well established in Maak and Pless (J Bus Ethics 66:99–115, 2006a; Responsible leadership, 2006b) among others.
Keywords: Ethical Behavior; insurance firms; Risk modeling; Prudence